104th Fresno County Bar Association Annual Bar Banquet-TorNino's - Watkins, Howard::::::::: (1986)
Charles Small facing left: County Counsel attorneys: Ruth Ratzlaff, Cynthia Manzer, Howard Watkins, Max Robinson, Robert Wash, Vincent McGraw, James Waterman, Thomas Riggs and Georgia York